2014
DOI: 10.1088/1367-2630/16/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Self-excited current oscillations in a resonant tunneling diode described by a model based on the Caldeira–Leggett Hamiltonian

Abstract: The quantum dissipative dynamics of a tunneling process through double barrier structures is investigated on the basis of non-perturbative and non-Markovian treatment. We employ a Caldeira-Leggett Hamiltonian with an effective potential calculated self-consistently, accounting for the electron distribution. With this Hamiltonian, we use the reduced hierarchy equations of motion in the Wigner space representation to study non-Markovian and nonperturbative thermal effects at finite temperature in a rigorous mann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 106 publications
(252 reference statements)
1
68
0
Order By: Relevance
“…[62][63][64] Because the HEOM approach is computationally heavy, a variety of algorisms have been developed to deal with dissipative dynamics in realistic situations. [65][66][67][68][69][70][71][72] It has been applied to the study of multi-dimensional vibrational spectroscopies, [52][53][54][55] photosynthetic antenna systems, [58][59][60][73][74][75][76] fermion systems, [77][78][79] quantum ratchets, 80 resonant tunneling diodes, 81,82 and dissociation of tightly bounded electron-hole pairs. 83 While the applicability of the HEOM approach continues to expand, the basic nature of the hierarchy elements has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64] Because the HEOM approach is computationally heavy, a variety of algorisms have been developed to deal with dissipative dynamics in realistic situations. [65][66][67][68][69][70][71][72] It has been applied to the study of multi-dimensional vibrational spectroscopies, [52][53][54][55] photosynthetic antenna systems, [58][59][60][73][74][75][76] fermion systems, [77][78][79] quantum ratchets, 80 resonant tunneling diodes, 81,82 and dissociation of tightly bounded electron-hole pairs. 83 While the applicability of the HEOM approach continues to expand, the basic nature of the hierarchy elements has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…To get a qualitative picture of the mechanism behind the current oscillations, several authors have previously solved the time-independent Schrödinger equation (obtained eigenstates and energies) for a sub-region of the device in question 17,18,40 . Here, we do the same.…”
Section: Effects Of Scatteringmentioning
confidence: 99%
“…In contrast, as shown earlier in this section, we found that current oscillations are driven by the time-dependent potential difference between the EQW and MQW. Sakurai and Tanimura worked within a hierarchy-equationof-motion formalism and also observed intrinsic current oscillations in RTDs 18,19 . To explain their results, they performed a similar bound-state analysis.…”
Section: E Frequency Of the Current-density Oscillations Effect Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Both forms are difficult to solve and, as a result, a plethora of numerical methods for evolving the Wigner function propagation have been developed. These have involved (i) the integral form of Moyal's equation [20][21][22][23][24][25], (ii) reduction of the Moyal equation to a Boltzmann-like equation [26,27], (iii) propagation of Gaussian and coherent states [28][29][30][31], (iv) Monte Carlo schemes in which the Wigner function is contracted by averaging over stochastic trajectories of pure-states [32][33][34][35], and (v) evolving the density matrix in the coordinate representation [36,37].…”
Section: Introductionmentioning
confidence: 99%